False messages about the coronavirus: legitimacy and manipulation in the class struggle - Lima, Guilherme Da Silva; Calazans, Marcos Moraes; Massi, Luciana [UNESP] (Centro Int Estudios Superiores Comunicacion Amer Latina-ciespal, 2021)
This paper aims to analyze the first false messages composition on the new coronavirus and Covid-19 that circulated in Brazil. The analysis problematize the relationships between form and content that give legitimacy to the messages and how they are inserted in the class struggle. We used the contributions of the Circle, especially Volochinov, on the nature of language associated with contributions from the field of historical and dialectical materialism, to analyze 11 messages, two of which were analyzed deeply. The results indicated that false communications are inserted in the class struggle seeking to manipulate the interlocutor and they appropriated and mobilized elements, mainly from the spheres of Science and Journalism, to give the effect of credibility and legitimacy.
Keywords: fake news; coronavirus; class struggle; ideology; manipulation